DETERMINANTS OF COMMUNITY ACTUAL BEHAVIOR IN THE WASTE BANK PROGRAM: THE MEDIATING ROLE OF INTENTION - Agnes Azzahra Trisida; Tiara Safira Almadani; Bambang Eko Samiono (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the effects of knowledge, attitude, and facilities on community actual behavior in the waste bank program in West Jakarta, with intention as a mediating variable, based on the Theory of Planned Behavior. Waste management remains a critical environmental issue in West Jakarta due to the limited availability of waste bank facilities and low community participation, which contribute to environmental and public health problems. A quantitative approach was employed using survey data collected from 110 waste bank facility users selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that knowledge and attitude do not have a significant direct effect on actual behavior but significantly influence actual behavior indirectly through intention, with attitude emerging as the strongest predictor of intention. In contrast, facilities have a significant direct effect on actual behavior without mediation by intention. Intention also positively and significantly affects actual behavior. These findings suggest that community participation is driven by two complementary pathways, namely an attitudinal cognitive pathway through intention and a structural pathway through facilities. This study recommends improving waste sorting facilities and strengthening community intentions through education simultaneously to support the sustainability of the waste bank program.